Peningkatan Pengetahuan Penjamah Makanan di Lingkungan Usaha Mikro, Kecil, dan Menengah (UMKM) melalui Sosialisasi Higiene dan Sanitasi Penyelenggaraan Makanan - Fadilatus Sukma Ika Noviarmi; Neffrety Nilamsari; Salsabila Al Firdausi; Nur Anisah Rahmawati; Mochammad Sholehhudin (BADAN PENERBIT STIEPARI PRESS, 2025)
Community services about hygiene and sanitation for food handlers is necessary to prevent the food produced from physical, chemical, and biological contamination, and to avoid causing diseases in humans. This is very important because there are 20 million cases of food poisoning every year in Indonesia. Activity of this community services consists of socialization hygiene and sanitation principles in the food processing process. The socialization is delivered in the form of lectures presentation, the provision of booklet and the distribution of cleaning tools for vendors. This community service in the Gubeng Airlangga area of Surabaya. The activity was attended by 49 participants who are food handlers from micro, small, and medium enterprises MSMEs, consisting of 17 men and 32 women. The result showed a significant improvement with the average pre-test score rising from 68.17 to 85.71 in the post-test. Thirty-two participants (65.3%) achieved a 'very good' knowledge category after attending the socialization. Wilcoxon Test indicated a significant difference between the pre-test and post-test results (p-value = 0.000 < 0.05). The conclusion of this activity is that the socialization method through lectures and media in the form of slide shows and pocket books is considered effective to increasing the knowledge of food handlers. Recommendations for future activities include continuous assistance, the development of a more comprehensive socialization program that combines lecture methods, practical demonstrations, and field visits, as well as active involvement from the government to provide support for Adequate hygiene and sanitation facilities for MSMEs, integration of technology aspects in upcoming socialization programs.